Early human handling in non-weaned piglets: Effects on behaviour and body weight - Oliveira, Daiana de [UNESP]; Costa, Mateus José Rodrigues Paranhos da [UNESP]; Zupan, Manja; Rehn, Therese; Keeling, Linda J. (Elsevier B.V., 2015)
Early handling of animals including tactile stimulation (TS) has been shown to have beneficial effects on the physical and psychological development of species where considerable maternal interaction, e.g. in the form of licking, already occurs. But little is known about the magnitude of these effects, if any, in species without this natural mechanism. Piglets from 13 litters (N=127) were subjected to four treatments: AH - all piglets in a litter received TS; NH - none of the piglets in a litter received TS; 50/50H - half of a litter received TS and 50/50NH - half of a litter did not receive TS. The TS was performed by a human stroking the back of the piglet for 2 min from 5 to 35 days of age. At 4 weeks of age the piglets were tested twice in an open-field/human-approach test, with either a familiar (F) or an unfamiliar person (U). Body weight was measured at birth, 5,9 and 12 weeks of age. In the tests, AH and 50/50H piglets allowed more physical contact, regardless of the familiarity of the person (AH: 22.5 +/- 2.3 F; 24.1 +/- 2.3 U, 50/50H: 18.1 +/- 2.2 F; 25.3 +/- 2.2 U, P = 0.05). Additionally, AH piglets vocalized least and were least often in the perimeter zone (PZ) of the arena (AH grunts: 6.0 +/- 0.8, P= 0.002; 12.8 +/- 0.8, P = 0.0005; 18.1 +/- 0.8, P= 0.08; AH PZ: 3.9 +/- 0.8, P=0.009; 9.1 +/- 0.8, P= 0.003; 12.6 +/- 0.7, P= 0.004 in isolation, stationary and moving person phase, respectively). In contrast, NH piglets vocalized most and were most often in the PZ. 50/50NH had higher body weights at 12 weeks than 50/50H, whereas AH and NH piglets were intermediate (AH: 36.9 +/- 0.9, NH: 35.6 +/- 1.0, 50/50H: 34.2 +/- 1.3, 50/50NH: 37.8 +/- 1.3, P= 0.03). This study suggests that early handling changed the way piglets reacted to challenging situations in that handled piglets showed behaviour suggesting they were less fearful in a novel environment and less fearful of being handled by people in general. Interestingly though, the early handling did not result in the same beneficial effects on the physical development of the piglets, as handled piglets were not heavier. Instead, it was the 50/50NH piglets that were the heaviest, implying that the daily presence of a human moving around in the pen to handle the 50/50H piglets seemed to stimulate weight gain.
Keywords: Human-animal interactions; Handling; Pigs; Psychological development; Growth; Welfare